Class A G-protein-coupled receptor (GPCR) dimers and bivalent ligands - Hiller, Christine; Kühhorn, Julia; Gmeiner, Peter (Journal of Medicinal Chemistry, 2013)
G-protein-coupled receptors (GPCRs) represent the largest family of membrane proteins involved in cellular signal transduction and are activated by various different ligand types including photons, peptides, proteins, but also small molecules like biogenic amines. Therefore, GPCRs are involved in diverse physiological processes and provide valuable drug targets for numerous diseases. Emerging body of evidence suggests that GPCRs exist as monomers or cross-react forming dimers and higher-ordered oligomers. In this Perspective we will review current biochemical and biophysical techniques to visualize GPCR dimerization, functional consequences of homo- and heterodimers, and approaches of medicinal chemists to target these receptor complexes with homo- and heterobivalent ligands. © 2013 American Chemical Society.

Covalent agonists for studying G protein-coupled receptor activation - Weichert, Dietmar; Kruse, Andrew C.; Manglik, Aashish; Hiller, Christine; Zhang, Cheng; Hübner, Harald; Kobilka, Brian K.; Gmeiner, Peter (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Structural studies on G protein-coupled receptors (GPCRs) provide important insights into the architecture and function of these important drug targets. However, the crystallization of GPCRs in active states is particularly challenging, requiring the formation of stable and conformationally homogeneous ligand-receptor complexes. Native hormones, neurotransmitters, and synthetic agonists that bind with low affinity are ineffective at stabilizing an active state for crystallogenesis. To promote structural studies on the pharmacologically highly relevant class of aminergic GPCRs, we here present the development of covalently binding molecular tools activating Gs-, Gi-, and Gq-coupled receptors. The covalent agonists are derived from the monoamine neurotransmitters noradrenaline, dopamine, serotonin, and histamine, and they were accessed using a general and versatile synthetic strategy. We demonstrate that the tool compounds presented herein display an efficient covalent binding mode and that the respective covalent ligand-receptor complexes activate G proteins comparable to the natural neurotransmitters. A crystal structure of the β2-adrenoreceptor in complex with a covalent noradrenaline analog and a conformationally selective antibody (nanobody) verified that these agonists can be used to facilitate crystallogenesis.
UnivIS-Import:2015-03-09:Pub.2014.nat.dchph.lphch.covale
Keywords: Chemical biology; Chemical probes; Structural biology

Functionally selective dopamine D2/D3 receptor agonists comprising an enyne moiety - Hiller, Christine; Kling, Ralf; Heinemann, Frank Wilhelm; Meyer, Karsten; Hübner, Harald; Gmeiner, Peter (Journal of Medicinal Chemistry, 2013)
Dopaminergics of types 1 and 2 incorporating a conjugated enyne as an atypical catechol-simulating moiety were synthesized in enantiomerically pure form and investigated for their metabolic stability. Radioligand binding studies indicated high affinity to D-like receptors. The test compounds were evaluated for their ability to differentially activate distinct signaling pathways. Measurement of D- and D-mediated [ S]GTPγS incorporation in the presence of coexpressed Gα and Gα subunits showed significantly biased receptor activation for several test compounds. Thus, the 2-azaindolylcarboxamide (S)-2a exhibited substantial functional selectivity for D-promoted G activation over G coupling. The most significant bias was determined for the triazolylalkoxy-substituted benzamide (S)-2c that displayed higher potency for G activation than for G coupling at the D subtype. Functional selectivity for β-arrestin recruitment over G activation was observed for the biphenylcarboxamide (R)-1 and the 2-benzothiophenylcarboxamide (S)-2d, whereas the 2-substituted azaindole (S)-2a preferred β-arrestin recruitment compared to G coupling. © 2013 American Chemical Society.

GPCRs als hochrelevante Targets für die Wirkstoffentwicklung - Hiller, Christine; Gmeiner, Peter (BioSpektrum, 2014)
G protein-coupled receptors are involved in numerous physiological processes and provide attractive drug targets for diverse diseases. However, the development of selective, efficacious drugs targeting this family of membrane proteins remains challenging due to multidimensional selectivity profiles of GPCR-agonists and antagonists. Selective GPCR ligands have the potential to induce or stabilize individual receptor conformations or to preferentially bind one particular receptor subtype. © 2014 Springer-Verlag Berlin Heidelberg. Literatur:.

GPCRs as highly relevant targets for the development of efficient drugs - Hiller, Christine; Gmeiner, Peter (BioSpektrum, 2014)
UnivIS-Import:2018-09-05:Pub.2014.nat.dchph.lphch.gpcrsa

Molecular Determinants of Biased Agonism at the Dopamine D2 Receptor - Weichert, Dietmar; Banerjee, Ashutosh; Hiller, Christine; Kling, Ralf; Hübner, Harald; Gmeiner, Peter (Journal of Medicinal Chemistry, 2015)
UnivIS-Import:2015-03-11:Pub.2015.nat.dchph.lphch.molecu